Study of Joule-Thomson cooling effect due to leakage in compressed gas pressure vessels - Ai, Gang (2014)
The reliability of pressure vessels in Compressed Natural Gas (CNG) ship is very important because there is very high pressure inside the CNG container (up to 250 bar). A key way to maintaining the integrity of pressure vessels is the principle of Leak-Before-Failure (LBF). However, the temperature of leaking CNGwill drop due to Joule-Thomson cooling effect when CNGpasses through the crack. The localized cooling effect on the steel plates may affect the ductile to brittle transition failure.Hitherto, the LBF is applied to piping system without considering the temperature change of steel material caused by Joule-Thomson cooling effect. Simulation and experiments thus are desirable to verify the effect in a narrow leaking crack on pressure vessel. By this means, the application of LBF may need to be corrected. The narrow leakingcrack canbe considered to comprisemanyshort and equivalent parts along the through-wall direction. Each part can be considered as a small throttling type nozzle. An iterative calculation program in MATLAB has been developed in this thesis. Due to the similarity on Joule-Thomson effect, argon is chosen as a substitute for CNG with safety in mind. The program is developed to calculate the pressure, velocity, density, temperature, viscosity, thermal conductivity and heat transfer coefficient of leaking argon through the crack by considering the Joule-Thomson effect. The calculated results of temperature, pressure and heat transfer coefficient of argon along the crack depth are used as boundary conditions in COMSOL FEA program for the heat transfer and thermal stress simulation. In MATLAB iterative calculations, the initial argon pressure inside the pressure vessel is the maximum pressure of 91 bar during test. The initial temperature is room temperature of 30 oC. Solutions of pressure, velocity and density of leaking argon of each small space inside the crack are firstly obtained after inputting the crack dimensions and roughness parameters. The pressure of leaking Argon drops from 91 bar at the entrance of the crack to 9.5 bar at the exit of the crack. The velocity of leaking Argon through the crack does not change much. The density of leaking Argon drops from 150.7 kg/m3 at the entrance of the crack to 16.8 kg/m3 at the exit of the crack. Then the temperature of leaking argon inside the crack is calculated. The temperature of leaking Argon decreases from 30 oC at the entrance of the crack to 0.04 oC at the exit of the crack. With the pressure and temperature data, the viscosity, thermal conductivity and heat transfer coefficient of leaking argon in crack are obtained. Having obtained the properties of leaking argon in the crack from MATLAB, the heat transfer and thermal stress simulation is implemented to predict the temperature and stress distribution of the pressure vessel wall around the crack. A three-dimensional quarter model of mild steel plate is created by utilizing the COMSOL Multiphysics program. The heat transfer of metal and gas is treated as a one-way coupling problem due to rapid expansion of gas during leaking through the crack. Calculated argon properties are input into COMSOL as boundary conditions on the crack surface. The simulated lowest temperature of steel agrees well with the experimental result. The maximum Von Mises stress value near the crack tip is 3.3 GPa.The value is much higher than the yield stress (0.22 GPa) of mild steel in this research. Experiments are carried out by a designed and machined J-T rig to verify the J-T effect in the crack. An artificialthrough-thickness crack inthe center of a round test plate is fabricated using the liquefied Nitrogen cracking method.The crack width and roughness are measured by a feeler gauge and TalyScan 150, respectively. These values are used as input parameters in the MATLAB iterative calculations. The test plate as a cover of pressure vessel is assembled with the pressure vessel to perform the Joule-Thomson experiment. A web-camera connected to a computer is used to monitor and record the display of the pressure gauge. The thermocouples are connected to a TDS-302 data logger from which temperature data can be recorded and printed.During the Argon test, the highest pressure in the pressure vessel is 91 bar. It is found that the lowest temperature near the crack caused by the Joule-Thomson effect is 12.5 oC. Good agreement of the lowest steel temperature is found between the simulation and experimental test result.